Multi-elemental analysis of some traditional medicinal plants from Marghalla Hill National Park, Pakistan - Saboon; Arshad, Muhammad; Bibi, Yamin; Ahmad, Muhammad Sheeraz (Journal of Pure and Applied Agriculture, 2023)
Multi-nutritional effect of plants is a gift from nature. Instead of having a great source of food, large variety of plants are also used as medicine due to presence of large amount of nutritive and non-nutritive compounds. The present study was conducted on the traditional medicinal plants from Marghalla Hills National Park in 2020-2021 in the Department of Botany, PMAS Arid Agriculture Lab for their multi-elemental analysis. In the qualitative phytochemical analysis most of plants species were found rich in term of nutritive and non-nutritive compounds. While in the quantitative analysis, C. arvensis, S. mocroofitiana and P. plebeium showed high total phenolic content (120.86 ± 0.44 μg GAE/mg, 113 ± 0.26 μg GAE/mg, 103.94 ± 0.19 μg GAE/mg) and flavonoid content (83.47 ± 0.32μg QE/mg, 46.32 ± 0.29 μg QE/mg and 38.52 ± 0.30 μg QE/mg). High scavenging ability and total antioxidant ability was observed in the extracts of S. heteromalla (98.37 μg/ml; 99.3637 μg/ml) and C. arvensis (147.096 μg/ml; 102.34637 μg/ml). While high reducing ability was observed in P. plebeium. The high nutritive value was observed in C. arvensis and L. aphaca with the values of 407.28 ± 0.49 kcal/100 g and 407.78 ± 0.59 kcal/100g. Several micro and macro minerals were observed in different concentration in. The results of the present study revealed that the traditional medicinal plants are high in their nutritive and non-nutritive components which provide the strong relationship of their medicinal effect. This study will provide a base for the researcher to explore these plants for their biological activities. © 2022 Department of Agricultural Sciences, AIOU